PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURALTHINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII5 SMPN 29 PEKANBARU - Alhidayah, Risa Alhidayah; Saragih, Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is a learning process and mathematics achievementare not optimal in the class VIII5 SMP 29 Pekanbaru in the second semester academic years 2013/2014.The research was classroom action research to improve learning process and mathematicsachievementwith applied the cooperative learning think pair square structural approach. This research consist of two cycles, and at the end of every cycle carried out mathematics achievement test. Data collected through observation and mathematicsachievement test.Analysis data of observation was performed with narrative descriptive analysis and analysis data of mathematicsachievement was performed with descriptive statistical analysis. Result of this research showed an increase in students from the base score with the percentage 12% to 67% on the first test and 60% on the second test. Results of this research indicates that the cooperative learning think pair square structural approachcan improvelearning process and studentsmathematicsachievement math class VIII5 SMPN29 Pekanbaru. Key words: Mathematics Achievement, Cooperative learning, Think Pair Square, Class action research